Wielding the past to voice the future: an exploration of Indigenous Australians’ sustained call to be heard (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
This essay explores why ‘voice’ has been a sustained desire for Indigenous Australians throughout history. By placing past efforts surrounding recognition, citizenship and self-determination on a continuum of progress, this text presents an argument for an unwavering, Indigenous voice to be enshrined in the Australian Constitution in order to serve the best interests of Aboriginal Australians.